Perinatal mental health and well-being in fathers - Conde, Ana (2022)
Research focusing on fathers' perinatal mental health is recent and less substantial than the research focusing on mothers. Nevertheless, mental health problems and disorders are common in fathers during the perinatal period and should be the focus of attention, namely in planning promotion, preventive, and remedial interventions, with expected benefits for all of the family over time.